CFD parametric studies for global performance improvement of open refrigerated display cabinets - Gaspar, Pedro Dinis (2019)
A detailed CFD modelling of an open refrigerated display cabinet has been formulated in a previous study. Some modifications are introduced in order to perform parametric studies dealing with low-cost geometrical and functional characteristics for improvement of the global performance and energy efficiency. The parametric studies are devoted to the analysis of the thermal response and behaviour inside the food conservation space influenced by (1) air flow rate through the evaporator heat exchanger; (2) air curtain behaviour; (3) hole dimensions and distribution of the back panel; (4) discharge and return grilles angles; and (5) flow deflectors inside the internal duct. The analysis of the numerical predictions from the parametric studies allows the development of an optimized model for the conception of an open refrigerated display cabinet with a more adequate configuration. The numerical predictions of the optimized model show lower product temperature and reduced electrical energy consumption, allowing the improvement of the food safety and the energy rationalization of the refrigeration equipment.